2011
DOI: 10.2139/ssrn.1965962
|View full text |Cite
|
Sign up to set email alerts
|

Testing the General Validity of the Heckscher-Ohlin Theorem: The Natural Experiment of Japan

Abstract: We exploit Japan's 19 th century opening up to trade to test a general formulation of the Heckscher-Ohlin theorem. This formulation is based on Ohlin's measure of factor scarcity where autarky factor prices impose a refutable prediction on the economy's factor content of trade. Our test combines factor price data in Japan's autarky period with commodity trade data and a technology matrix in Japan's early free trade period. Our technology matrix is derived from a major Japanese survey of agricultural techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The Heckscher-Ohlin model shows that corporate strategy is directly related to the internal (workforce) environmental factors in a country (Bernhofen & Brown, 2011). For example, companies in a country with a relatively more abundant workforce have an advantage in terms of corporate strategy relative to those companies in a country with less abundant workforce (Forman & Lancioni, 2002 the study conducted by Kabadayi, Eyuboglu and Thomas (2007) indicated that the internal factors affected managers in strategy decision making.…”
Section: Effects Of the Internal Environments On Corporate Strategymentioning
confidence: 99%
“…The Heckscher-Ohlin model shows that corporate strategy is directly related to the internal (workforce) environmental factors in a country (Bernhofen & Brown, 2011). For example, companies in a country with a relatively more abundant workforce have an advantage in terms of corporate strategy relative to those companies in a country with less abundant workforce (Forman & Lancioni, 2002 the study conducted by Kabadayi, Eyuboglu and Thomas (2007) indicated that the internal factors affected managers in strategy decision making.…”
Section: Effects Of the Internal Environments On Corporate Strategymentioning
confidence: 99%
“…The main contribution of this paper is that instead of expanding the theory by adding and relaxing assumptions to make it more compatible with observed international trade data, I use an historical episode where thè all else equal' assumption of the HOV model is plausible, but nonetheless the model makes non-trivial predictions. Bernhofen and Brown (2011) use the natural experiment of Japan's move from autarky to free trade in the mid-nineteenth century to test what they refer to, following Deardor (1982), as the general validity of the Heckscher-Ohlin model, or HOD (Heckscher-Ohlin-Deardor ). Relying on numerous sources for factor prices and production techniques, they nd empirical support for the main testable prediction of the HOD, which states that evaluated at factor's autarky prices, the value of the factor content of trade is (weakly) positive.…”
Section: Relation To the Literaturementioning
confidence: 99%
“…In addition to using more standardized data, from a more recent historical episode, the contribution of this paper relative to Bernhofen and Brown (2011) is that it tests one of the most special versions of the Heckscher-Ohlin model, maintaining all the strong assumptions of the HOV formulation, and not the most general formulation, which Bernhofen and Brown test. This allows for more intuitive results about the trade prediction, and it allows me to test not just the trade prediction, but also the Rybczynski eect, and the Factor Price Insensitivity prediction.…”
Section: Relation To the Literaturementioning
confidence: 99%
“…However, it requires compatible data of an economy observed under autarky and free trade. Bernhofen and Brown (2010) revisit the natural experiment of Japan to test (14). Since Bernhofen and Brown (2005) have already provided evidence that Japan experienced gains from trade, as discussed in section 2, we already know that the data environment fulfils the critical assumption of the theory.…”
Section: Figure 3: Heckscher-ohlin Price Predictionmentioning
confidence: 99%
“…As a result, there is something at stake in testing (14) since a rejection could not be explained by unmet assumptions. Bernhofen and Brown (2010) employ a self-constructed input-output matrix from around 1870 to obtain Japan"s factor content of trade during its early trading period F i =A 1870 T i (i=1865,..., 1876). When evaluating F i at the factor prices w 1850s in the late autarky period, they are unable to reject (14) for each single trading year.…”
Section: Figure 3: Heckscher-ohlin Price Predictionmentioning
confidence: 99%